Pengaruh Keadilan Distributif dan Prosedural Kompensasi terhadap Kepuasan Kerja dan Kinerja Perawat di RSU DR. H. RM. SOESELO di Slawi, Kabupaten Tegal, Jawa Tengah - Sulaefi, Sulaefi (Fakultas Ekonomi dan Bisnis, UNTAN, 2017)
This research examines the organizationa justice include distributive justice compensation and pocedural justicecompensation to employess performance both directly and indirectly influenced by job satisfaction. The population inthis study were all nurse employees in RSU DR. H. RM. SOESELO in Slawi, Tegal District are totaling 142 people.Data were collected by survey method is to provide a list of questionnaires directly to the resp4.ondent. Data analysistechniques in this study using analysis of SEM (Structural Equation Modeling) program operated by AMOS 21. Theresults showed that distributive justce compensation significant positive effect on job satisfaction, procedural justicecompensation significant positive effect on job satisfaction, distributive justice compensation are not significsantly toemployees performance, procedural justice compensation are not significantly to employees performance, jobsatisfaction significant positive effect on employees performace, job satisfaction as a mediating influence ofdistributive justice compensation and procedural justice compensation to employees performance.